The Effect of the Intensity of Happy Expression on Social Perception of Chinese Faces - Li, Yaning; Jiang, Zhongqing; Yang, Yisheng; Leng, Haizhou; Pei, Fuhua; Wu, Qi (Frontiers in Psychology, 2021)
Numerous studies have shown that facial expressions influence trait impressions in the Western context. There are cultural differences in the perception and recognition rules of different intensities of happy expressions, and researchers have only explored the influence of the intensity of happy expressions on a few facial traits (warmth, trustworthiness, and competence). Therefore, we examined the effect of different intensities of Chinese happy expressions on the social perception of faces from 11 traits, namely trustworthiness, responsibility, attractiveness, sociability, confidence, intelligence, aggressiveness, dominance, competence, warmth, and tenacity. In this study, participants were asked to view a series of photographs of faces with high-intensity or low-intensity happy expressions and rate the 11 traits on a 7-point Likert scale (1 = “not very ××,” 7 = “very ××”). The results indicated that high-intensity happy expression had higher-rated scores for sociability and warmth but lower scores for dominance, aggressiveness, intelligence, and competence than the low-intensity happy expression; there was no significant difference in the rated scores for trustworthiness, attractiveness, responsibility, confidence, and tenacity between the high-intensity and low-intensity happy expressions. These results suggested that, compared to the low-intensity happy expression, the high-intensity happy expression will enhance the perceptual outcome of the traits related to approachability, reduce the perceptual outcome of traits related to capability, and have no significant effect on trustworthiness, attractiveness, responsibility, confidence, and tenacity.